2011
DOI: 10.1128/aac.01835-09
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Encoded AmpC and CTX-M Extended-Spectrum β-Lactamases in Clinical Isolates of Proteus mirabilis from Korea

Abstract: Among 222 Proteus mirabilis clinical isolates collected from 17 hospitals in Korea in 2008, 28 (12.6%) and 8 (3.6%) isolates exhibited extended-spectrum ␤-lactamase (ESBL) and AmpC phenotypes, respectively. The most common type of ESBL gene identified by PCR and sequencing experiments was bla CTX-M-14a (n ‫؍‬ 12). The bla CTX-M-90 (n ‫؍‬ 4), bla CTX-M-15 (n ‫؍‬ 3), bla CTX-M-12 (n ‫؍‬ 3), bla CTX-M-2 (n ‫؍‬ 2), bla CTX-M-14b (n ‫؍‬ 1), bla TEM-52 (n ‫؍‬ 5), and bla SHV-12 (n ‫؍‬ 1) genes were also detected. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 24 publications
0
39
1
Order By: Relevance
“…The molecular epidemiology of ESBL-encoding genes in P. mirabilis isolated from humans varies widely between geographical regions. TEM types, especially TEM-52 and TEM-92, dominate in France and Italy (44,45), while CTX-M types are common in Israel (CTX-M-2), Poland (CTX-M-3), Japan (CTX-M-2), South Korea (CTX-M-14), and Argentina (CTX-M-2) (41,42,(46)(47)(48). Providencia species producing ESBL types other than CTX-M-2 have only been reported on a few occasions (49).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular epidemiology of ESBL-encoding genes in P. mirabilis isolated from humans varies widely between geographical regions. TEM types, especially TEM-52 and TEM-92, dominate in France and Italy (44,45), while CTX-M types are common in Israel (CTX-M-2), Poland (CTX-M-3), Japan (CTX-M-2), South Korea (CTX-M-14), and Argentina (CTX-M-2) (41,42,(46)(47)(48). Providencia species producing ESBL types other than CTX-M-2 have only been reported on a few occasions (49).…”
Section: Discussionmentioning
confidence: 99%
“…Although chromosomal integration of bla CTX-M and other genes encoding extended-spectrum ␤-lactamases is regarded as a relatively uncommon event (11,12), several studies have suggested that those events could be more common in P. mirabilis (2,8,9,19,28,32). Of 28 CTX-M-producing P. mirabilis clinical isolates collected in Korea, 21 carried bla CTX-M on the chromosome (28).…”
mentioning
confidence: 99%
“…1). Chromo- somally located bla CTX-M genes, including bla CTX-M-2 , bla CTX-M-12 , bla CTX-M-14 , bla CTX-M-15 , bla CTX-M-41 , and bla CTX-M-90 , have been found in several countries (9,11,20).…”
Section: Resultsmentioning
confidence: 99%